ICSID rules and regulations 2022 : administrative and financial regulations - institution rules - arbitration rules - conciliation rules : article-by-article commentary - International Centre for Settlement of Investment Disputes; Happ, Richard; Wilske, Stephan; Lewandowski, Ralf; Raynal, Mathilde (New York : Hart, 2022)
As a result of the fourth amendment of the Rules and Regulations, the legal framework of ICSID proceedings has been modernised, simplified and streamlined. A team of renowned practitioners and rising stars in the field of international arbitration have analysed these updated frameworks, which include the ICSID Arbitration Rules, the Conciliation Rules, the Institution Rules as well as the Administrative and Financial Regulations, to offer practical and theoretical guidance for experienced lawyers and beginners in the field
Includes bibliographical references and index.
Keywords: International commercial arbitration; Investments; International law